2019
DOI: 10.21203/rs.2.9193/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplex qPCR Facilitates Identification of Betaherpesviruses in Patients With Acute Liver Failure of Unknown Etiology

Abstract: Background: The etiology of acute liver failure (ALF) is often unknown and reported to be associated with herpesviruses in a number of cases. In this study, we examined for betaherpesviruses infections in patients with ALF of unknown etiology using a multiplex qPCR to Betaherpesviruses subfamily. Methods: Liver and serum samples from 27 patients with ALF of unknown etiology were analyzed with the aid of multiplex qPCR to identify betaherpesviruses. All positive samples were sequenced to confirm herpes infectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In general, the limit of detection of the pan‐herpes test performed in our study were 10‐400 genome copies per reaction 9 . This sensitivity is comparable to qPCR real time protocols described previously for some herpesviruses and also the qPCR protocol used in our laboratory 25,26 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In general, the limit of detection of the pan‐herpes test performed in our study were 10‐400 genome copies per reaction 9 . This sensitivity is comparable to qPCR real time protocols described previously for some herpesviruses and also the qPCR protocol used in our laboratory 25,26 …”
Section: Discussionsupporting
confidence: 76%
“…9 This sensitivity is comparable to qPCR real time protocols described previously for some herpesviruses and also the qPCR protocol used in our laboratory. 25,26 Our results showed that herpesviruses were co-detected in the participants' saliva before renal transplantation (32.8%) as well as 15-20 (56.1%) and 45-60 (52%) days after transplantation.…”
Section: Ta B L E 3 Herpesvirus Salivary Detection At the 3 Evaluatedmentioning
confidence: 70%
“…We present a retrospective study where hospitalized patients with signs and symptoms of moderate to severe COVID- The qPCR reaction for HHV-6 was performed using a primer and probe sequences for the U56 region of HHV-6. 17 To investigate the active infection, the HHV-6 detection was performed in the same samples used to detect SARS CoV-2, for this reason, the RNA extracted was used in this study. A saliva sample tested to intermediate replicative was used as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The qPCR reaction for HHV‐6 was performed using a primer and probe sequences for the U56 region of HHV‐6 17 . To investigate the active infection, the HHV‐6 detection was performed in the same samples used to detect SARS CoV‐2, for this reason, the RNA extracted was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative real-time PCR assay was applied to measure viral loads [18] using U56 and U37 regions to target HHV-6 A/B and HHV-7, respectively. Primers and oligonucleotide TaqMan probes are presented in Table 1.…”
Section: Real-time Multiplex Qpcr Analysismentioning
confidence: 99%